Using the RAPD-PCR technique to indentify the genetic ralationship of some Calothrix species isolated from cultural soil of the Dak Lak province - Hanh, Ho Sy; Hanh, Vo; Hong, Dang Diem (Academia Journal of Biology, 2006)
Five pure species of the genus Calothrix have been isolated from soil samples in the Daclac province and classified by the classical method. We have used the RAPD-PCR technique to explore the genetic relationship of these 5 Calothrix species. The results showed that 75 bands were multiplied by 3 random primers OPA4, OPA10 and OPL12; each of which on average had 25 bands for these Calothrix species. There were 74 polymorphic bands and one band was common marker for these species. The RAPD-PCR technique showed the genetic difference among these 5 species. The findings by using the RAPD-PCR technique were consistent with the results of classical methods.